Hubungan Pola Asuh Orang Tua dengan Kemandirian Anak Usia 4-6 Tahun di PAUD SKB Gudo Jombang - Mariati, Pipit; Lestari, Gunarti Dwi (J+PLUS UNESA, 2024)
This research aims to determine the relationship between parenting styles and the independence of children aged 4-6 years. This research uses a quantitative approach using questionnaire data collection techniques and documentation. Respondents in the research were 40 parents of students. In the validity and reliability test using the SPSS 23.0 formula with a significance level of 5%. Next, test normality and linearity using the Kolmogorov-smimnov formula with significance < 0.05% in SPSS 23.0. Then the inferential statistical hypothesis testing is carried out using the Pearson Product Moment Correlation formula. The results of research using hypothesis testing show that parenting patterns with the independence of children aged 4-6 years obtained a correlation coefficient level of 0.530 with a significance of 0.000 (P<0.05), which means that parenting patterns have a sufficient relationship with children's independence. 4-6 years old. It can be concluded that the relationship shows a significant level of relationship. The parenting style that parents apply plays a role in forming children's independence.